A three-point boundary value problem with an integral condition for a third-order partial differential equation. (31st January 2005) - Latrous, C.; Memou, A.
Abstract : We prove the existence and uniqueness of a strong solution for a linear third-order equation with integral boundary conditions. The proof uses energy inequalities and the density of the range of the operator generated.